A preparation method for directly constructing sulfur-doped iron-cobalt-nickel ternary oxide nanotubes and its products and applications
The sulfur-doped iron-cobalt nickel ternary oxide nanotubes are directly deposited on the current collector substrate by cyclic voltammetry, which solves the problems of active site loss and poor conductivity in the preparation of nanotube materials in the prior art, and achieves efficient electrode material preparation and excellent energy storage performance.
Patent Information
- Application Number
- CN202110754318.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-05
AI Technical Summary
There are two shortcomings in the preparation of the positive electrode nanotube materials of the existing secondary water-based zinc ion battery: the nanotube template materials need to be used to cause loss of active sites; non-conductive adhesives need to be added during the preparation process, which affects the conductivity and energy storage specific capacity of the electrode.
Cyclic voltammetry is used to directly deposit sulfur-doped iron-cobalt nickel ternary oxide nanotubes on the current collector substrate, avoiding the use of intermediate carrier materials and binders to achieve direct growth and application of nanotubes.
The direct growth and application of nanotubes without intermediate carrier materials and binders is achieved, and the effective activity and energy storage specific capacity of the electrode are improved. The discharge voltage platform reaches 1.3V-1.5V, and the energy storage specific capacity is about 3 times that of traditional powder materials.
Smart Images

Figure HDA0003146926600000011 
Figure HDA0003146926600000012 
Figure HDA0003146926600000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a method for directly constructing a sulfur-doped iron-cobalt-nickel ternary oxide nanotube preparation method and an application thereof as a secondary aqueous zinc ion battery positive electrode material. Background Art
[0002] Electrochemical energy storage is an important technology to solve the problems of uneven spatial distribution of new green energy sources such as solar energy and wind energy, and the mismatch between power supply energy density and the power grid. Among them, secondary aqueous zinc-ion batteries themselves have the characteristics of green and environmental protection, and are an important research object in the field of electrochemical energy storage. Energy density is one of the important indicators to measure the storage capacity of secondary aqueous zinc-ion batteries. It is the product of the specific capacity of battery energy storage and its discharge voltage platform. At present, the electrical energy storage performance of secondary aqueous zinc-ion batteries is mainly limited by the lack of active reaction centers in their positive electrode materials and the slow electron / ion transmission. According to the effective ion diffusion equation D eff =D0(ε / τ)(where D eff , D0, ε and τ represent the effective diffusion coefficient of ions in the electrode and electrolyte, the porosity of the electrode and the tortuosity of the pores, respectively. It can be determined that the nanomorphology with abundant transport channels (ε) and ordered diffusion paths (τ) is helpful to improve the effective diffusion coefficient of the carrier ion, that is, to improve the carrier ion diffusion kinetics of the electrode. At the same time, a higher electrode porosity can increase the specific surface area of the electrode, expose active sites, facilitate the insertion and extraction of carrier ions, and thus help to improve the specific capacity of the electrode. Based on this judgment, nanostructured materials are favored because they can provide a larger specific surface area and fully expose the reaction active centers. Among them, porous nanostructured materials such as nanotubes are particularly concerned because their hollow structures can provide convenient channels for ion transport, which is beneficial to the ion transport kinetics.
[0003] However, at present, the preparation of nanotube materials for the positive electrode of secondary aqueous zinc ion batteries has two shortcomings: (1) It needs to use nanotube template materials, such as carbon nanotubes. However, as one of the main materials for current collector conductivity, this type of carbon material cannot be directly used as the energy storage active center of the positive electrode of secondary aqueous zinc ion batteries. On the contrary, it will cause the loss of some active sites of the loaded active materials, which will limit the energy storage capacity of the electrode to a certain extent; (2) The secondary aqueous zinc ion nanotube positive electrode material usually prepared is a powder material, that is, carbon nanotubes are mixed and ground with active materials and binder substances, and the obtained powder material is then loaded on the surface of the current collector through a coating process. This preparation process cannot avoid the addition of non-conductive binders, and is affected by the mixing and coating processes, which can easily cause the interface resistance or contact resistance of the electrode to be large and the conductivity to be poor. At the same time, the mixed non-conductive binder will also cause the loss of some active sites of the active carrier.
[0004] So far, the methods for preparing non-polar metal compound nanotubes include high temperature and high pressure hydrothermal, solvent thermal method, arc method, laser ablation method, sol-gel chemical method, chemical vapor deposition method, and the template method widely used in recent years, the template can be a porous membrane of aluminum oxide or polycarbonate. However, the synthesis conditions of the above methods are relatively harsh, and high temperature, high pressure, laser or vacuum atmosphere are required. Among them, the subsequent template removal process of the template method needs to adopt chemical corrosion or high temperature decomposition method, so the composition and structure of the loaded active compound will be affected to a certain extent, and the price of some templates such as polycarbonate is relatively expensive. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for directly constructing sulfur-doped iron-cobalt-nickel ternary oxide nanotubes in view of the shortcomings of the above-mentioned prior art. The method does not require the use of intermediate carrier materials such as carbon nanotubes, etc., and directly grows along the surface of the current collector to obtain a nanotube structure, which can be directly used as a battery electrode without the intervention of a low-conductivity and non-energy storage active binder.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] A method for directly constructing sulfur-doped iron-cobalt-nickel ternary oxide nanotubes, using a current collector substrate as a working electrode, with the participation of a counter electrode and a reference electrode, 2+ , Fe 3+ 、Ni 2+ An aqueous solution of a sulfur source is used as a reaction solution, KCl ion electrolyte is added, and multi-sulfur-doped ternary (Fe, Co, Ni) oxide nanotubes are deposited on a current collector substrate using a cyclic voltammetry method.
[0008] According to the above scheme, Co in the reaction solution 2+ , Fe 3+ and Ni 2+ The concentration of the sulfur source is in the range of 0.005±0.0003M, and the concentration of the sulfur source is in the range of 0.01-0.2M based on the S element content. Further, the reaction solution is composed of a water-soluble cobalt salt, a water-soluble iron salt, a water-soluble nickel salt, a water-soluble sulfur source and water, wherein Co 2+ , Fe 3+ and Ni 2+ The concentration of is in the range of 0.005±0.0003M, and the concentration of the sulfur source is in the range of 0.05-0.2M. Wherein, the water-soluble cobalt salt and the water-soluble nickel salt are both nitrates, the water-soluble iron salt can be iron nitrate or iron chloride, the sulfur source is thiourea, etc., and the water is deionized water.
[0009] Furthermore, the reaction solution is composed of Co(NO3)2, Fe(NO3)3, Ni(NO3)2, thiourea and water, the concentration ratio of Co(NO3)2, Fe(NO3)3 and Ni(NO3)2 is 1:1:1, and the concentration ratio of thiourea to metal salt (Co(NO3)2 or Fe(NO3)3 or Ni(NO3)2) is in the range of 10:1-40:1.
[0010] According to the above scheme, the electrolyte for improving ion conductivity is potassium chloride, and its concentration in the reaction solution is controlled at 0.001M-0.005M.
[0011] According to the above scheme, during the cyclic voltammetry deposition process, the voltage scanning rate is 5mV s -1 , that is, the voltage on the surface of the current collector relative to the reference electrode is first increased by 5 mV s -1 From -1.2V to 0.2V, then -0.5mV s -1 The rate is reduced back to -1.2V to complete the first round of scanning, and then the scanning rate is maintained to complete subsequent scanning, for a total of ten rounds.
[0012] According to the above scheme, the current collector substrate can be either nickel foam or carbon cloth, such as Shanghai Hesen HCP330. 2 , the current collector geometric area is 1×2cm 2 Further, taking carbon cloth as an example, the carbon cloth current collector needs to be pretreated before being used as a working electrode, that is, the carbon cloth is placed in 10% HCl solution, ethanol and acetone for 10 minutes each, and then taken out and dried at a drying temperature of 60°C for 12 hours.
[0013] The sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared by the method of the present invention are uniformly covered on the surface of the current collector, with openings facing upward, uniform sizes, orderly arrangement, and no agglomeration. The sulfur-doped iron-cobalt-nickel ternary oxide nanotubes have an average width of about 200 nm, a uniform hollow size, and a nanosheet coating on the tube wall surface.
[0014] The sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared by the above method are used as the positive electrode material of secondary aqueous zinc-ion batteries for the first time. The open pore structure and high porosity of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes directly deposited on the surface of a current collector such as carbon cloth or nickel foam by the method of the present invention provide a guarantee for exposing abundant active sites (increasing specific surface area), and provide a transport channel and diffusion path for the diffusion of carrier ions. At the same time, the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes are tightly compounded with the current collector (carbon cloth or nickel foam, etc.), which improves the transmission efficiency of electrons.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] First, the present invention adopts a simple and convenient electrochemical cyclic voltammetry method to obtain sulfur-doped iron-cobalt-nickel ternary oxide nanotubes grown along the surface of any current collector substrate material. The preparation conditions are mild, at room temperature and pressure; the preparation process is simple and economical, and does not require the use of nanotube template materials without energy storage activity.
[0017] Second, the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes of the present invention can be directly grown along the surface of the current collector and have their own nanotube structure, and can be directly used as battery electrodes without the need for a binder with low conductivity and no energy storage activity.
[0018] Third, the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared by the present invention are used as the positive electrode of secondary aqueous zinc ion batteries (AZIBs) for the first time, successfully avoiding the loss of some active sites of the material due to the intervention of inactive intermediate carrier materials, and improving the effective activity of the electrode. The sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared by the present invention are evenly distributed along the surface of the carbon cloth or nickel foam current collector, with the opening facing upward. The hollow channels of the nanotubes provide a convenient way for the diffusion of carrier ions, which is beneficial to improving the diffusion kinetics of ions; and the pore wall is coated with a nano-thin sheet structure, which further increases the specific surface area of the active sites for the insertion and extraction of carrier ions, and promotes the energy storage capacity of the carrier ions. At the same current density, the energy storage capacity of the sulfur-doped iron-cobalt-nickel ternary oxide nanotube positive electrode described in the present invention in the application of secondary aqueous zinc ion batteries is about 3 times that of the positive electrode prepared from a mixture of Fe, Co, and Ni oxides.
[0019] Fourth, the iron, cobalt and nickel oxides selected for the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes of the present invention show a relative Zn / Zn 2+ The higher redox voltage increases the discharge voltage platform of the secondary aqueous zinc-ion battery to 1.3V-1.5V, which is equivalent to the manganese-based oxide positive electrode; its corresponding energy storage capacity is 0.3A·g -1 The current density can reach 140mAh g -1 BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM image of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared in Example 1.
[0021] Figure 2 This is a TEM image of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared in Example 1.
[0022] Figure 3 This is the XRD pattern of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared in Example 1.
[0023] Figure 4 This is the HRTEM image of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared in Example 1.
[0024] Figure 5 This is the XPS graph of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared in Example 1.
[0025] Figure 6 This is a CA charge-discharge curve diagram of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared in Example 1. DETAILED DESCRIPTION
[0026] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0027] In the following examples, the area of the counter electrode Pt sheet is 1.5×1.5 cm 2 , the area of nickel foam current collector is 1×2 cm 2 .
[0028] Example 1
[0029] A method for preparing sulfur-doped iron-cobalt-nickel ternary oxide nanotubes is carried out according to the following steps:
[0030] 1) Pretreatment of nickel foam current collector
[0031] Cut the nickel foam into 1×2cm pieces 2 The electrode was placed in 50 ml of 10% HCl solution, ethanol and acetone, each ultrasonicated for 10 minutes, and then placed in a 60°C electric oven for 12 hours to serve as a working electrode.
[0032] 2) Preparation of sulfur-doped iron-cobalt-nickel ternary oxide nanotubes
[0033] The nickel foam pretreated in step 1) was placed as a working electrode in 50 ml of a mixed salt solution (with water as solvent) containing 0.005±0.0003M Co(NO3)2·6H2O, 0.005±0.0003M Fe(NO3)3, 0.005±0.0003M Ni(NO3)2·6H2O, 0.001M KCl and 0.05M (NH2)2CS, and then placed together in an ultrasonic bath for 10 seconds;
[0034] At room temperature, the carbon cloth in the mixed salt solution was used as the working electrode, the Pt sheet was used as the counter electrode, and the saturated calomel electrode was used as the reference electrode. The working electrode clip, counter electrode clip, and reference electrode clip of the Shanghai Chenhua CHI600e electrochemical workstation were connected respectively, and the cyclic voltammetry scanning program was selected. The program setting conditions were: the scanning starting voltage was -1.2 V, and then 5 mV s -1 The voltage was increased to 0.2 V at a scan rate of -5 mV s -1 The scan rate is reduced to -1.2V, and one scan is completed. The total number of scans is ten. After the scan is completed, sulfur-doped iron-cobalt-nickel ternary oxide nanotubes growing along the surface of the current collector are found.
[0035] 3) Drying of sulfur-doped iron-cobalt-nickel ternary oxide nanotubes
[0036] The sulfur-doped iron-cobalt-nickel ternary oxide nanotube positive electrode prepared in step 2) was taken out and rinsed with a large amount of deionized water until the pH of the rinse water solution was close to 6.89. The rinsed sample was then placed on filter paper and placed in a vacuum drying oven after the deionized water accumulated on its surface was absorbed. The drying oven was set to a temperature of 60°C, a vacuum degree of -0.9Mpa, and a time of 12h.
[0037] Example 2
[0038] The difference between this embodiment and embodiment 1 is that in the mixed salt solution, the concentration of (NH2)2CS is 0.1M.
[0039] Example 3
[0040] The difference between this embodiment and embodiment 1 is that in the mixed salt solution, the concentration of (NH2)2CS is 0.2M.
[0041] As Figure 1 As shown, the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared by the present invention are uniformly covered on the surface of the current collector, with openings facing upward, uniform sizes, orderly arrangement, no agglomeration, and the pore walls are coated with nanosheets. Figure 2 It can be seen that the average width of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes is about 200 nm, the hollow size is consistent, and the surface of the tube wall is covered with a very thin lamellar structure.
[0042] from Figure 3 It can be seen that except for the background diffraction peak of the current collector (here nickel foam), since the sample has not been subjected to high-temperature heat treatment, its crystallinity is not as good as the nickel foam base material, so its signal is easily weakened by the base background, but the sample diffraction peak can match the corresponding iron, cobalt and nickel oxide diffraction peaks respectively. It is apparent that the compound prepared by this method is a mixture of corresponding metal oxides.
[0043] from Figure 4 It can be judged that the XPS spectrum shows the signal peaks of Ni 2p3 / 2 (856.4eV), Ni 2p1 / 2 (873.7eV), Fe2p3 / 2 (713.5eV), Fe 2p1 / 2 (725.6eV), Co 2p3 / 2 (781.2eV), Co 2p1 / 2 (797.6eV), O 1s (531.2eV) and S2p1 / 2 (168.6eV), indicating that the composition of the compound obtained by this preparation method includes Ni, Fe, Co, O and S. Figure 3 The diffraction peak results of XRD can prove that the compound is a sulfur-doped iron-cobalt-nickel ternary metal oxide.
[0044] from Figure 5 The interlayer spacing observed in Figure 3 The interlayer spacing of NiO and CoOOH on specific surfaces is consistent, which further proves that the compound is a mixture of oxides of phase iron, cobalt and nickel.
[0045] The application of the sulfur-doped iron-cobalt-nickel ternary oxide nanotubes prepared by the present invention in secondary aqueous zinc ion batteries is mainly achieved by measuring their energy storage capacity and comparing it with the energy storage capacity of the corresponding metal oxide mixture powder electrode material.
[0046] The energy storage capacity was determined by using the prepared sulfur-doped iron-cobalt-nickel ternary oxide nanotubes as the positive electrode and a zinc sheet with a purity of 99.9% as the counter electrode and reference electrode. The areas of the positive electrode and the zinc sheet were 1×2 cm 2 and 2.5×2.5cm 2 , saturated zinc sulfate solution was used as the electrolyte, and the open circuit voltage of the working electrode relative to the zinc sheet was about 1.5 V. The absolute value of the charge and discharge current density was set to 0.3 A g -1 First, at -0.3A·g -1 The electrode was discharged at a current density of 0.3A·g until the discharge voltage dropped from 1.5V to 0.2V. -1 The battery was charged at a current density of 2.2 V and the charge and discharge were repeated five times.
[0047] The preparation process of the metal oxide (Fe2O3, NiO, Co2O3) mixture powder electrode material for comparison is as follows: weigh 1.6g, 0.75g and 1.65g of Fe2O3, NiO and Co2O3 powders with a purity greater than 99% respectively, put them in a mortar and grind for 5 minutes. Then add 1.15g Li-P superconducting carbon black and 0.56g polyvinylidene fluoride to the mortar, and add dimethylformamide dropwise while stirring until a paste is formed, which is applied to the pretreated nickel foam surface. The nickel foam area is 1×2cm 2And, coating quality is controlled at 1g·cm -2 After that, it is placed in an oven at 60°C for 12 hours, and after the polyvinylidene fluoride is volatilized, it can be used as the positive electrode of a secondary aqueous zinc ion battery.
[0048] from Figure 6 It can be seen that at the same discharge current density, the energy storage capacity of the secondary aqueous zinc ion battery with sulfur-doped iron-cobalt-nickel ternary oxide nanotubes as the positive electrode is about three times that of the positive electrode prepared with a mixture of Fe, Co, and Ni oxide powders.
[0049] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for directly constructing sulfur-doped iron-cobalt-nickel ternary oxide nanotubes, characterized in that: The current collector substrate is used as the working electrode, and in the presence of the counter electrode and the reference electrode, a Co 2+ , Fe 3+ 、Ni 2+ and an aqueous solution of a sulfur source as a reaction solution, KCl ion electrolyte is added, and sulfur-doped iron-cobalt-nickel ternary oxide nanotubes are deposited on a current collector substrate using a cyclic voltammetry method; The current collector is nickel foam or carbon cloth, and the sulfur source is thiourea; The reaction solution is composed of Co(NO3)2, Fe(NO3)3, Ni(NO3)2, thiourea and water, wherein the concentration range of Co(NO3)2, Fe(NO3)3 and Ni(NO3)2 is 0.005 ± 0.0003M; the concentration range of thiourea is 0.05 M-0.2 M; the concentration of KCl is controlled at 0.001-0.005 M; the scanning program setting conditions of the cyclic voltammetry method are: the scanning starting voltage is -1.2 V, and then the scanning voltage is 5 mV s -1 The voltage was increased to 0.2 V at a scan rate of -5 mV s -1 The scan rate is reduced to -1.2 V, and one scan is completed. The total number of scans is ten. The sulfur-doped iron-cobalt-nickel ternary oxide nanotubes are uniformly covered on the surface of the current collector, with openings facing upward, uniform sizes, orderly arrangement, no agglomeration, and the tube walls are coated with nanosheets; The sulfur-doped iron-cobalt-nickel ternary oxide nanotube is used as a positive electrode material for a secondary aqueous zinc ion battery.
2. The method for directly constructing sulfur-doped iron-cobalt-nickel ternary oxide nanotubes according to claim 1, characterized in that: The counter electrode is a Pt counter electrode, and the reference electrode is a saturated calomel electrode.
Citation Information
Patent Citations
Composite positive electrode material as well as preparation method and application thereof in zinc ion battery
CN111554931A
Method for manufacturing graphite film electro-deposited metal oxide for supercapacitor electrode and supercapacitor comprising the same
KR1020130140946A